1991
DOI: 10.1021/om00053a006
|View full text |Cite
|
Sign up to set email alerts
|

A tricyclic ring system of six carbon and five boron atoms from monoalkylbenzene and five formal borene units

Abstract: Products of RC6H,*5BNR', are the highest borylated species to be formed in reactions between dehalogenation products of F,BN(i-Pr), with monoalkylbenzenes. The structures are cages, each consisting of a five-, six-, and seven-membered ring, in which the carbon skeleton has been split into C,, C,, and C3 units, as shown by singlacrystal X-ray structure determinations. Mass spectroscopic and 'H, llB, and 13C NMR and elemental analyses are reported.Generally, reactions of the six-electron species carbene with aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A tricyclic ring/cage system of RC 6 H 5 ·5BNR' 2 products were formed by reactions between dehalogenation products of F 2 BN( i -Pr) 2 with monoalkylbenzenes using monoglyme as the co-solvent. 274 Hung et al 275 prepared linear and cyclic perfluorinated polyethers through the ionic polymerization of a trifluorovinyl ether alcohol (CF 2 =CFOR f CH 2 OH, R f = CF 2 CF(CF 3 )OCF 2 CF 2 ) and the subsequent fluorination of the polyfluorinated polyethers (Scheme 32). They found that without a solvent, linear polymers with M n values up to 29,000 were produced, while in glyme solution, cyclic oligomers were major products and a cyclic dimer was obtained in yields up to 60%.…”
Section: Uses In Organic Reactionsmentioning
confidence: 99%
“…A tricyclic ring/cage system of RC 6 H 5 ·5BNR' 2 products were formed by reactions between dehalogenation products of F 2 BN( i -Pr) 2 with monoalkylbenzenes using monoglyme as the co-solvent. 274 Hung et al 275 prepared linear and cyclic perfluorinated polyethers through the ionic polymerization of a trifluorovinyl ether alcohol (CF 2 =CFOR f CH 2 OH, R f = CF 2 CF(CF 3 )OCF 2 CF 2 ) and the subsequent fluorination of the polyfluorinated polyethers (Scheme 32). They found that without a solvent, linear polymers with M n values up to 29,000 were produced, while in glyme solution, cyclic oligomers were major products and a cyclic dimer was obtained in yields up to 60%.…”
Section: Uses In Organic Reactionsmentioning
confidence: 99%
“…Aminoborylene 3a (R = H) was detected by Thompson et al . in an argon matrix after co-deposition of laser ablated boron atoms with ammonia, while Meller and co-workers have successfully trapped derivatives of 3 . The barrier to [1,2]-H migration in 3a , 27 kcal mol -1 from theory, is significantly larger than that in 1a . Both 1a and 3a have singlet ground states; the triplet state of 1a lies significantly higher in energy …”
Section: Introductionmentioning
confidence: 99%